2012
DOI: 10.1016/j.scriptamat.2012.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh strength and high plasticity in TiAl intermetallics with bimodal grain structure and nanotwins

Abstract: Nanostructured intermetallics generally exhibit high strength but limited plasticity due to the covalent nature of their bonding. In this study, high-pressure torsion followed by annealing was used to produce TiAl intermetallics with two microstructural features: (i) bimodal microstructure composed of nanograins and submicrometer grains; and (ii) nanotwins. An exceptional performance, combining ultrahigh yield strength, ~2.9 GPa, and high strain to failure, ~14%, was achieved with micropillar compression tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 37 publications
4
68
0
1
Order By: Relevance
“…In the present study, we investigate the influence of pressure on the formation of the ductile β-phase in γ-based TiAl alloys, which is not only of fundamental interest, but is also most relevant to modelling high-pressure deformation techniques, such as high-pressure torsion, in order to achieve severe plastic deformation [11][12][13][14][15] and high-pressure near-net-shape forging [16][17][18][19]. These deformation processes operate at pressures up to 7 GPa and forces exceeding 1 GN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigate the influence of pressure on the formation of the ductile β-phase in γ-based TiAl alloys, which is not only of fundamental interest, but is also most relevant to modelling high-pressure deformation techniques, such as high-pressure torsion, in order to achieve severe plastic deformation [11][12][13][14][15] and high-pressure near-net-shape forging [16][17][18][19]. These deformation processes operate at pressures up to 7 GPa and forces exceeding 1 GN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of different SPD processing techniques are available to enhance the upper limit of mechanical properties of a specific alloy [9][10][11][12][13] but it is also important to study achieving superior properties by bonding dissimilar metals through a procedure such as fusion welding. Alternatively, processing by HPT was applied recently for the consolidation of metal powders and for fabricating dissimilar metallic systems based on aluminum and magnesium: for example, Al-Fe, 14 Al-Mg, 15 Al-Ni, 16 Al-Ti, 17 Al-W, 18,19 and Mg-Zn-Y. 20 Nevertheless, the practical difficulties associated with these processes include a requirement for a high processing temperature, 16,17,19,20 the need for a two-step process of cold/hot compaction prior to consolidation by HPT 18 and the inherent damage that may be introduced in the HPT anvils because of the stacking of fine hard powders in the depressions on the anvil surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these works are focused on HPT processing using bulk samples, consolidation of powders using HPT has recently received much attention [23][24][25][26][27][28][29][30] . The HPT method was recently applied for production of nanostructured intermetallics with ultrahigh strength and high ductility from their elemental constituents 33,34 . The method was applied to powder mixtures of the Al-Ni and Al-Ti systems and it was found that in addition to powders consolidation and grain refinement, nanograined intermetallics were formed.…”
Section: Introductionmentioning
confidence: 99%